Измерение амплитудной диаграммы направленности и частотной характеристики антенн ISM-диапазона с помощью WiFi-маршрутизаторов - Садченко, А.В.; Кушниренко, О.А.; Цевух, И.В.; Валянский, И.А.; Чихрай, Ю.С. (Технология и конструирование в электронной аппаратуре, 2016)
Предложена методика измерения частотной характеристики и диаграммы направленности антенн, предназначенных для беспроводного доступа в диапазоне частот 2,4 ГГц с использованием трансивера WiFi-маршрутизаторов. Приведены результаты лабораторного измерения амплитудной диаграммы направленности и частотной характеристики семиэлементной антенны типа «волновой канал». Запропоновано методику вимірювання частотної характеристики і діаграми спрямованості антен, призначених для бездротового доступу в діапазоні частот 2,4 ГГц з використанням трансивера WiFi-маршрутизаторів. Наведено результати лабораторного вимірювання амплітудної діаграми спрямованості і частотної характеристики семиелементної антени типу «хвильовий канал». The aim of this work is to develop a simplified procedure for measuring the amplitude RP and frequency characteristics of antennas for the rapid assessment of electromagnetic environment during deployment of wireless networks, when the requirements for measurement accuracy are not critical. In this article we propose to use as a UHF calibrated power generator a standard Wi-Fi router with a coaxial output, i.e. with the possibility to connect an external antenna. Certified routers 802.11n standard of 2.4 GHz band, regardless of the manufacturer, provide the following parameters: output power range of 20-100 mW, receiver sensitivity of 80-85 dBm, dynamic range of the receiver - 90 dBm. Using system settings of the router allows one to rapidly change the frequency in the range of 2400-2483.5 MHz with a step of 5-20 MHz. The practical value of the proposed methodology for measuring Wi-Fi antennas characteristics consists in substantial saving of time and costs during deployment and adjusting of wireless networks. This method can be successfully used for testing city wireless video surveillance systems and public access points to the local and global resources of city network.